Credit Frictions, Collateral and the Cyclical Behavior of the Finance Premium - Pierre-Richard Agenor; George J. Bratsiotis; Damjan Pfajfar (Macroeconomic Dynamics, 2014)
This paper examines the behavior of the finance premium after technology and monetary shocks in a dynamic stochastic general equilibrium (DSGE) model where borrowers use a fraction of their production (output) as collateral. We show that this simple framework is capable of producing a countercyclical finance premium, while matching the well-documented stylized facts of macro dynamics. A key feature is the endogenous derivation of the default probability from break-even conditions, which results in the loan rate being set as a countercyclical finance premium over the cost of borrowing from the central bank. The latter is shown to provide an accelerator effect through which shocks can amplify the loan spread and the dynamic response of macro variables.
Additional information: working paper version (preprint)
Keywords: 330; Credit Frictions; Business Cycles; Collateral; Finance Premium; Loan Spread